N-Acetylcysteine Prevents the Spatial Memory Deficits and the Redox-Dependent RyR2 Decrease Displayed by an Alzheimer’s Disease Rat Model - More, Jamileth; Galusso, Nadia; Veloso, Pablo; Montecinos, Luis; Finkelstein, José Pablo; Sanchez, Gina; Bull, Ricardo; Valdés, José Luis; Hidalgo, Cecilia; Paula-Lima, Andrea (Frontiers in Aging Neuroscience, 2018)
We have previously reported that primary hippocampal neurons exposed to synaptotoxic amyloid beta oligomers (AβOs), which are likely causative agents of Alzheimer’s disease (AD), exhibit abnormal Ca2+ signals, mitochondrial dysfunction and defective structural plasticity. Additionally, AβOs-exposed neurons exhibit a decrease in the protein content of type-2 ryanodine receptor (RyR2) Ca2+ channels, which exert critical roles in hippocampal synaptic plasticity and spatial memory processes. The antioxidant N-acetylcysteine (NAC) prevents these deleterious effects of AβOs in vitro. The main contribution of the present work is to show that AβOs injections directly into the hippocampus, by engaging oxidation-mediated reversible pathways significantly decreased RyR2 protein content but increased single RyR2 channel activation by Ca2+ and caused considerable spatial memory deficits. AβOs injections into the CA3 hippocampal region impaired rat performance in the Oasis maze spatial memory task, decreased hippocampal glutathione levels and overall content of plasticity-related proteins (c-Fos, Arc, RyR2) and increased ERK1/2 phosphorylation. In contrast, in hippocampus-derived mitochondria-associated membranes (MAM) AβOs injections increased RyR2 levels. Rats fed with NAC for 3-weeks prior to AβOs injections displayed comparable redox potential, RyR2 and Arc protein contents, similar ERK1/2 phosphorylation and RyR2 single channel activation by Ca2+ as saline-injected (control) rats. NAC-fed rats subsequently injected with AβOs displayed the same behavior in the spatial memory task as control rats. Based on the present in vivo results, we propose that redox-sensitive neuronal RyR2 channels partake in the mechanism underlying AβOs-induced memory disruption in rodents.